A unique phenomenon of oral-anal contact between ticks observed in two tick species Ixodes ricinus and Dermacentor reticulatus - Alicja Buczek; Katarzyna Bartosik; Weronika Buczek; Alicja M. Buczek; Dorota Kulina; Joanna Kulisz; Krzysztof Tomasiewicz (Annals of Agricultural and Environmental Medicine, 2018)
For the first time in the world literature, the presented study describes oral-anal contact between two sympatric Ixodes ricinus and Dermacentor reticulatus ticks, which are the vectors of many pathogens in Europe. Among the specimens collected in nature, an I. ricinus male was found with the hypostome and chelicerae inserted in the anal aperture of a D. reticulatus female. Given the biological and physiological traits of both species and microorganisms colonising these arthropods, it seems that the interspecific oral-anal contacts between ticks may be an unknown alternative route of transmission of pathogenic and symbiotic microorganisms present in ticks’ alimentary tract, faeces, body surface, and in the haemolymph and organs, taking place when the male’s mouthparts are inserted into the female’s body. The authors suggest that interspecific contacts between ticks in natural conditions can contribute to the spread of some icroorganisms among different tick species and their hosts..